2023
DOI: 10.1016/j.jtcvs.2021.03.077
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation after cardiac surgery: A systematic review and meta-analysis

Abstract: Objective: New-onset post-operative atrial fibrillation (POAF) after cardiac surgery is common, with rates up to 60%. POAF has been associated with early and late stroke, but its association with other cardiovascular outcomes is less known. The objective was to perform a meta-analysis of the studies reporting the association of POAF with perioperative and long-term outcomes in cardiac surgery. M ethod s: We performed a systematic review and a meta-analysis of studies presenting outcomes for cardiac surgery bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 123 publications
1
26
0
Order By: Relevance
“…Our trial revealed a lower incidence of POAF compared with other studies. 18,19 This is probably because of our strict inclusion and exclusion criteria, which eliminated patients at increased risk of POAF.…”
Section: Discussionmentioning
confidence: 99%
“…Our trial revealed a lower incidence of POAF compared with other studies. 18,19 This is probably because of our strict inclusion and exclusion criteria, which eliminated patients at increased risk of POAF.…”
Section: Discussionmentioning
confidence: 99%
“…Although POAF has been considered temporary and rather harmless, there was even an association with long-term mortality, stroke, and long-standing persistent atrial fibrillation. 20 Although a causal relationship between POAF and adverse events has not been established, the following randomized controlled trial 21 is important in this context because it shows an effective way to reduce POAF without increasing the risk of postoperative complications. The authors randomly assigned 420 adult patients without pre-existing atrial fibrillation to undergo posterior left pericardiotomy or no intervention during elective cardiac surgery.…”
Section: Surgical Treatment Of Coronary Artery Diseasementioning
confidence: 99%
“…One important risk factor for AF is surgery, and AF developing during the days following surgery is termed postoperative AF (POAF). POAF typically occurs 1-3 days after surgery [ 3 ] and portends a 5-fold higher risk of chronic AF [ 4 ] and a 2-fold higher risk of stroke and mortality [ 5 , 6 ] . Rates of POAF are 15%-42% after cardiac surgery [ 7 ] and 10%-20% after non-cardiac surgery [ 6 , 8 , 9 ] .…”
Section: Introductionmentioning
confidence: 99%